Fast Fashion dan Tantangan Keberlanjutan Industri Halal Perspektif Etika Produksi dan Konsumsi Islam - Afaf Dwi Safitri; Lilik Rahmawati (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2025)
The fashion industry is experiencing continuous acceleration. Increased social and economic competition is occurring in society to expand the boundaries of consumer demand. Fast fashion companies have successfully built this business model by relying on cheap labor and the resulting social, economic, and environmental impacts. The method used in this study is qualitative research with a literature study approach and an understanding of the meaning of social or humanitarian phenomena examined through descriptive analysis using the Islamic economic theory framework. The results show that the fast fashion industry has exploited the environment and even labor rights, which has had an impact on the economy, society, and health. Based on Islamic production ethics, it is clearly explained in the Qur'an that production practices must bring benefits to humans without causing harm, based on the four main principles of the Islamic economic system, namely, monotheism, balance, free will, and responsibility. Meanwhile, Islamic consumption ethics avoid wastefulness (tabzir) and unnecessary spending (isyraf), so that consumption behavior can provide long-term benefits for both worldly and afterlife. This study emphasizes the importance of collaboration between the government, stakeholders, and the community in creating a sustainable production system in accordance with Islamic values.